Deaths associated with pneumonic plague, 1946-2017 - Salam, AP; Rojek, A; Cai, E; Raberahona, M; Horby, P (Centers for Disease Control and Prevention, 2020)
The death rate for persons with treated pneumonic plague is often reported as 50%, but firm evidence for this figure is minimal. We conducted a meta-analysis of articles reporting the death rate for persons treated for pneumonic plague. The rate was 17%, substantially lower than the frequently cited 50%.